Microbial Complexity of Oral Cavity of Healthy Dogs Identified by Mass Spectrometry and Next-Generation Sequencing - Portilho, Fábio V. R. [UNESP]; Nóbrega, Juliano [UNESP]; de Almeida, Beatriz O. [UNESP]; Mota, André R. [UNESP]; de Paula, Carolina L. [UNESP]; Listoni, Fernando J. P. [UNESP]; Bosco, Sandra M. G. [UNESP]; Oliveira, Alana L. [UNESP]; Cunha, Maria de Lourdes R. S. [UNESP]; Ribeiro, Márcio G. [UNESP] (MDPI, 2023)
The high complexity of the oral microbiota of healthy dogs and the close exposure of humans to companion animals represent a risk of the transmission of potential zoonotic microorganisms to humans, especially through dog bites, including multidrug-resistant ones. Nonetheless, a limited number of comprehensive studies have focused on the diversity of the microorganisms that inhabit the oral cavities of healthy dogs, particularly based on modern molecular techniques. We investigated bacterial and fungal organisms in the oral cavities of 100 healthy dogs based on a combination of conventional and selective microbiological culture, mass spectrometry (MALDI-TOF MS), and next-generation sequencing. In addition, in vitro antimicrobial susceptibility patterns of isolates and mecA resistance gene were assessed. A total of 213 bacteria and 20 fungi were isolated. Staphylococcus pseudintermedius (40/100 = 40%), α-hemolytic Streptococcus (37/100 = 37%), and Pasteurella stomatis (22/100 = 22%) were the most prevalent bacteria diagnosed by microbiological culture and MALDI-TOF MS, whereas Aspergillus (10/100 = 10%) was the most common fungi identified. Based on next-generation sequencing of selected 20 sampled dogs, Porphyromonas (32.5%), Moraxella (16.3%), Fusobacterium (12.8%), Conchiformibius (9.5%), Bergeyella (5%), Campylobacter (3.8%), and Capnocytophaga (3.4%) genera were prevalent. A high multidrug resistance rate was observed in Staphylococcus pseudintermedius isolates, particularly to azithromycin (19/19 = 100%), penicillin (15/19 = 78.9%), and sulfamethoxazole/trimethoprim (15/19 = 78.9%). In addition, the mecA resistance gene was detected in 6.1% (3/49) of coagulase-positive staphylococci. Here, we highlight the microbial complexity of the oral mucosa of healthy dogs, including potential zoonotic microorganisms and multidrug-resistant bacteria, contributing with the investigation of the microbiota and antimicrobial resistance patterns of the microorganisms that inhabit the oral cavity of healthy dogs.
Keywords: 16S rRNA gene; canine oral microbiota; dog bites; large-scale sequencing; MALDI-TOF MS; mecA gene